THE IMPLEMENTATION OF RR-PSO AS INVERSION ALGORITHM TO DELINEATE SUBSURFACE STRUCTURE IN GUNDIH FIELD AT CCS PROJECT - Prasetyawan, Ageng
Carbon Capture and Storage (CCS) is one of the mitigation options to cut the amount of carbon dioxide (CO2) in the atmosphere by capturing CO2 gas in the earth's atmosphere and then injected into the earth, in this case, CO2 is injected into a reservoir in a rock formation. The resistivity contrast of the reservoir in a rock formation is important to delineate the reservoir and subsurface structures in the study area. The location of this research is generally in the Basin area of East Java. Reservoir delineation is done by the time-domain electromagnetic (TDEM) method. In this study begins by making an approach model from TDEM data obtained, by making forward modeling of TDEM 1D Grounded Wire, to obtain apparent resistivity. After that to find the model or parameters of the data, the inversion modeling is done. In this study, we applied inversion modeling using the Regressive-regressive Particle Swarm Optimization (RR-PSO) algorithm. RR-PSO algorithm has several disadvantages including, this algorithm is constrained in delineating thin layers, layers that are more than 1500 m, and layers with small resistivity contrast. However, by integrating the results from earlier research supporting data, this algorithm can delineate the location of the Ngrayong reservoir used in the CCS project and delineate subsurface structures in the study area